The Colonate in Justinian's Reign. - Sirks, A. J. B. (Journal of Roman Studies, 2008)
The article presents the study on the colonate during the reign of Eastern Roman Emperor Justinian 1 and his famous Codes. It states that every research of the serfdom of the Later Roman Empire is faced with the legal sources in Justinian's and Theodosius' Codes. It cites that since the codes consist of fragments of imperial constitutions, it is alluring to view them as fragments intrinsically, as not related historical facts. It contends that Justinian was expressive about his codification, which includes all constitutions gained in the Gregorian, Hermogenian and Theodosian Codes. There is a potential that there are some points that the codification were governed by customary, unwritten or unrecorded law, which was the intention accomplished by Justinian.